Geniposide Attenuates Oxygen-glucose Deprivation/Recovery-induced Retinal Ganglion Cell Injury via Akt/Nrf-2 Signaling Pathway - Hu, Ming-Hai; Chen, Dekun; Wu, Xiuyu; Ren, Guo-Feng (Current Medicinal Chemistry, 2025)
BackgroundGlaucoma is an eye disease. Its pathological process involves retinal ischemia-reperfusion (I/R), which causes irreversible blindness in patients. Geniposide (Gen), a bioactive iridoid glycoside extracted from the fruit of gardenia, exhibits many biological effects, such as anti-oxidative stress, anti-inflammation, anti-apoptosis, anti-endoplasmic reticulum stress, and anti-thrombotic effects. However, its therapeutic potential for the retinal I/R injury remains unclear. This study investigated the protective effect of Gen against I/R injury by inhibiting abnormal reactive oxygen species (ROS) and retinal neuron apoptosis.MethodsWe used oxygen-glucose deprivation/reoxygenation (OGD/R) to induce R28 cells to mimic the pathological process of I/R in glaucoma. We conducted CCK-8 analysis and TUNEL staining to examine cell proliferation and apoptosis in glaucoma. Western blotting was used to assay the expressions of apoptosis and Akt/Nrf-2 pathway-related proteins.ResultsThe production of ROS was detected by using the corresponding kit. Cell viability decreased, whereas TUNEL staining-positive cells and ROS production increased after the OGD/R injury. The contents of cleaved caspase-3 and Bax/Bcl-2 increased after the OGD/R injury. Treatment with 200 μM of Gen effectively improved the cell viability and suppressed cell apoptosis and ROS production. In addition, Gen could significantly promote the activation of the Akt/Nrf-2 signaling pathway in R28 cells, which was blocked by the inhibition of Akt/Nrf-2. We in vivo verified the neuroprotective effect of Gen by establishing an acute high intraocular pressure (aHIOP) model and obtained similar results to those of the in vitro experimental results.ConclusionHence, it can be suggested that Gen provides neuroprotection against the OGD/R-induced injury of R28 cells by activating the Akt/Nrf-2 signaling pathway, which is beneficial for the clinical treatment of glaucoma.
Keywords: ischemia-reperfusion